Correlação do nível da mielomeningocele com a função motora e o nível neurológico do segmento medular - Michelle Antunes Coutinho (2013)
The myelomeningocele (MMC) is the most serious congenital malformation of the central nervous system (CNS) for failure of the neural tube to close. What is known as a general pattern of MMC severity is that the higher its level, the worse the motor deficit, but there are patients who have clinical manifestations that contradict this precept: high MMC without motor deficits, and low MMC with major deficits. Objective: To evaluate the relationship among the macroscopic level of MMC, motor function and neurological level of the affected spinal segment. Methods: A cross-sectional study was conducted in a population of 28 patients operated on by the same neurosurgeon. The patients were divided into age groups of up to three years old, ages three to five, between six and seven and eight to 11 years old. We evaluated the macroscopic level of MMC, neurological level of the affected spinal segment and functional performance, through Gross Motor Function Test (GMFM), an instrument that assesses motor function quantitatively. Conclusion: Our results suggest that there is no direct correlation among the macroscopic level of myelomeningocele, motor function and neurological level of the affected spinal segment. In 71.42% of evaluated patients it was observed rather the opposite of what is established in literature: more neurological damage in patients with lower lesions and better functional performance in patients with higher lesions. Although our results do not show significant statistical differences, the data are part of a relevant preliminary study.